Effects of electronic coupling and electrostatic potential on charge transport in carbon-based molecular electronic junctions - McCreery, Richard L. (Beilstein Journal of Nanotechnology, 2016)
Molecular junctions consisting of 2–20 nm thick layers of organic oligomers oriented between a conducting carbon substrate and a carbon/gold top contact have proven to be reproducible and reliable, and will soon enter commercial production in audio processing circuits. The covalent, conjugated bond between one or both sp2-hybridized carbon contacts and an aromatic molecular layer is distinct from the more common metal/molecule or silicon/molecule structures in many reported molecular junctions. Theoretical observations based on density functional theory are presented here, which model carbon-based molecular junctions as single molecules and oligomers between fragments of graphene. Electronic coupling between the molecules and the contacts is demonstrated by the formation of hybrid orbitals in the model structure, which have significant electron density on both the graphene and the molecule. The energies of such hybrid orbitals correlate with tunneling barriers determined experimentally, and electronic coupling between the two graphene fragments in the model correlates with experimentally observed attenuation of transport with molecular layer thickness. Electronic coupling is affected significantly by the dihedral angle between the planes of the graphene and the molecular π-systems, but is absent only when the two planes are orthogonal. Coupling also results in partial charge transfer between the graphene contacts and the molecular layer, which results in a shift in electrostatic potential which affects the observed tunneling barrier. Although the degree of partial charge transfer is difficult to calculate accurately, it does provide a basis for the “vacuum level shift” observed in many experiments, including transport and ultraviolet photoelectron spectroscopy of molecular layers on conductors.
Keywords: molecular junction electron transport density functional theory molecular devices

(untitled) - Metzger, R. M. (Chem. Rev., 2015)

(untitled) - McCreery, R. L.; Yan, H.; Bergren, A. J. (Phys. Chem. Chem. Phys., 2013)

(untitled) - McCreery, R. L.; Bergren, A. J. (Adv. Mater., 2009)

(untitled) - Heath, J. R. (Annu. Rev. Mater. Res., 2009)

(untitled) - Amdursky, N.; Marchak, D.; Sepunaru, L.; Pecht, I.; Sheves, M.; Cahen, D. (Adv. Mater., 2014)

(untitled) - Aradhya, S. V.; Meisner, J. S.; Krikorian, M.; Ahn, S.; Parameswaran, R.; Steigerwald, M. L.; Nuckolls, C.; Venkataraman, L. (Nano Lett., 2012)

(untitled) - Chen, W.; Widawsky, J. R.; Vázquez, H.; Schneebeli, S. T.; Hybertsen, M. S.; Breslow, R.; Venkataraman, L. (J. Am. Chem. Soc., 2011)

(untitled) - Venkataraman, L.; Park, Y. S.; Whalley, A. C.; Nuckolls, C.; Hybertsen, M. S.; Steigerwald, M. L. (Nano Lett., 2007)

(untitled) - Li, Z.; Smeu, M.; Ratner, M. A.; Borguet, E. (J. Phys. Chem. C, 2013)

(untitled) - DiBenedetto, S. A.; Facchetti, A.; Ratner, M. A.; Marks, T. J. (J. Am. Chem. Soc., 2009)

(untitled) - Solomon, G. C.; Andrews, D. Q.; Van Duyne, R. P.; Ratner, M. A. (J. Am. Chem. Soc., 2008)

(untitled) - Lindsay, S. M.; Ratner, M. A. (Adv. Mater., 2007)

(untitled) - Luo, L.; Choi, S. H.; Frisbie, C. D. (Chem. Mater., 2011)

(untitled) - Kim, B.; Choi, S. H.; Zhu, X.-Y.; Frisbie, C. D. (J. Am. Chem. Soc., 2011)

(untitled) - Choi, S. H.; Kim, B.; Frisbie, C. D. (Science, 2008)

(untitled) - Yoon, H. J.; Shapiro, N. D.; Park, K. M.; Thuo, M. M.; Soh, S.; Whitesides, G. M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Cademartiri, L.; Thuo, M. M.; Nijhuis, C. A.; Reus, W. F.; Tricard, S.; Barber, J. R.; Sodhi, R. N. S.; Brodersen, P.; Kim, C.; Chiechi, R. C.; Whitesides, G. M. (J. Phys. Chem. C, 2012)

(untitled) - Nijhuis, C. A.; Reus, W. F.; Whitesides, G. M. (J. Am. Chem. Soc., 2010)

(untitled) - Akkerman, H. B.; Kronemeijer, A. J.; Harkema, J.; van Hal, P. A.; Smits, E. C. P.; de Leeuw, D. M.; Blom, P. W. M. (Org. Electron., 2010)

(untitled) - Van Hal, P. A.; Smits, E. C. P.; Geuns, T. C. T.; Akkerman, H. B.; De Brito, B. C.; Perissinotto, S.; Lanzani, G.; Kronemeijer, A. J.; Geskin, V.; Cornil, J.; Blom, P. W. M.; De Boer, B.; et al. (Nat. Nanotechnol., 2008)

(untitled) - Akkerman, H. B.; Blom, P. W. M.; de Leeuw, D. M.; de Boer, B. (Nature, 2006)

(untitled) - Green, J. E.; Wook Choi, J.; Boukai, A.; Bunimovich, Y.; Johnston-Halperin, E.; DeIonno, E.; Luo, Y.; Sheriff, B. A.; Xu, K.; Shik Shin, Y.; Tseng, H.-R.; Stoddart, J. F.; et al. (Nature, 2007)

(untitled) - DeIonno, E.; Tseng, H.-R.; Harvey, D. D.; Stoddart, J. F.; Heath, J. R. (J. Phys. Chem. B, 2006)

(untitled) - Vilan, A.; Yaffe, O.; Biller, A.; Salomon, A.; Kahn, A.; Cahen, D. (Adv. Mater., 2010)

(untitled) - Yu, X.; Lovrinčić, R.; Kraynis, O.; Man, G.; Ely, T.; Zohar, A.; Toledano, T.; Cahen, D.; Vilan, A. (Small, 2014)

(untitled) - Li, Y.; Calder, S.; Yaffe, O.; Cahen, D.; Haick, H.; Kronik, L.; Zuilhof, H. (Langmuir, 2012)

(untitled) - Seitz, O.; Vilan, A.; Cohen, H.; Hwang, J.; Haeming, M.; Schoell, A.; Umbach, E.; Kahn, A.; Cahen, D. (Adv. Funct. Mater., 2008)

Nanoelectrochemistry - McCreery, R. (Electron Transport and Redox Reactions in Solid-State Molecular Electronic Devices, 2015)

(untitled) - McCreery, R.; Bergren, A.; Morteza-Najarian, A.; Sayed, S. Y.; Yan, H. (Faraday Discuss., 2014)

(untitled) - Yan, H.; Bergren, A. J.; McCreery, R.; Della Rocca, M. L.; Martin, P.; Lafarge, P.; Lacroix, J. C. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Sayed, S. Y.; Fereiro, J. A.; Yan, H.; McCreery, R. L.; Bergren, A. J. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Bergren, A. J.; McCreery, R. L. (Annu. Rev. Anal. Chem., 2011)

(untitled) - Anariba, F.; Steach, J. K.; McCreery, R. L. (J. Phys. Chem. B, 2005)

(untitled) - Kondratenko, M.; Stoyanov, S. R.; Gusarov, S.; Kovalenko, A.; McCreery, R. L. (J. Phys. Chem. C, 2015)

(untitled) - Bergren, A. J.; McCreery, R. L.; Stoyanov, S. R.; Gusarov, S.; Kovalenko, A. (J. Phys. Chem. C, 2010)

(untitled) - Salomon, A.; Boecking, T.; Seitz, O.; Markus, T.; Amy, F.; Chan, C.; Zhao, W.; Cahen, D.; Kahn, A. (Adv. Mater., 2007)

(untitled) - Cahen, D.; Kahn, A. (Adv. Mater., 2003)

(untitled) - Braun, S.; Salaneck, W. R.; Fahlman, M. (Adv. Mater., 2009)

(untitled) - Ishii, H.; Sugiyama, K.; Ito, E.; Seki, K. (Adv. Mater., 1999)

(untitled) - Hwang, J.; Wan, A.; Kahn, A. (Mater. Sci. Eng., R, 2009)

(untitled) - Saha, S.; Roy, R. K.; Ayers, P. W. (Int. J. Quantum Chem., 2009)

Aryl Diazonium Salts: New Coupling Agents in Polymer and Surface Science - McCreery, R. L.; Bergren, A. J. (Diazonium reagents in molecular electronics, 2012)

(untitled) - Yan, H.; Bergren, A. J.; McCreery, R. L. (J. Am. Chem. Soc., 2011)

(untitled) - Wu, J.; McCreery, R. L. (J. Electrochem. Soc., 2009)

(untitled) - Wu, J.; Mobley, K.; McCreery, R. L. (J. Chem. Phys., 2007)

(untitled) - McCreery, R. L.; Wu, J.; Kalakodimi, R. P. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Kumar, R.; Yan, H.; McCreery, R. L.; Bergren, A. J. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Mujica, V.; Ratner, M. A. (Chem. Phys., 2001)

(untitled) - Lacroix, J. C.; Chane-Ching, K. I.; Maquère, F.; Maurel, F. (J. Am. Chem. Soc., 2006)

(untitled) - Sancho-García, J. C.; Pérez-Jiménez, A. J. (J. Chem. Phys., 2008)

(untitled) - Fereiro, J. A.; Kondratenko, M.; Bergren, A. J.; McCreery, R. L. (J. Am. Chem. Soc., 2015)

(untitled) - Fereiro, J. A.; McCreery, R. L.; Bergren, A. J. (J. Am. Chem. Soc., 2013)

(untitled) - Bonifas, A. P.; McCreery, R. L. (Nat. Nanotechnol., 2010)

(untitled) - Fracasso, D.; Valkenier, H.; Hummelen, J. C.; Solomon, G. C.; Chiechi, R. C. (J. Am. Chem. Soc., 2011)

(untitled) - Guédon, C. M.; Valkenier, H.; Markussen, T.; Thygesen, K. S.; Hummelen, J. C.; van der Molen, S. J. (Nat. Nanotechnol., 2012)

(untitled) - Rabache, V.; Chaste, J.; Petit, P.; Della Rocca, M. L.; Martin, P.; Lacroix, J.-C.; McCreery, R. L.; Lafarge, P. (J. Am. Chem. Soc., 2013)

(untitled) - Valkenier, H.; Guédon, C. M.; Markussen, T.; Thygesen, K. S.; van der Molen, S. J.; Hummelen, J. C. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Darwish, N.; Díez-Pérez, I.; Da Silva, P.; Tao, N.; Gooding, J. J.; Paddon-Row, M. N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Van Dyck, C.; Ratner, M. A. (Nano Lett., 2015)

(untitled) - Van Dyck, C.; Geskin, V.; Cornil, J. (Adv. Funct. Mater., 2014)

(untitled) - Guerrero, A.; Marchesi, L. F.; Boix, P. P.; Ruiz-Raga, S.; Ripolles-Sanchis, T.; Garcia-Belmonte, G.; Bisquert, J. (ACS Nano, 2012)

(untitled) - Shpaisman, H.; Seitz, O.; Yaffe, O.; Roodenko, K.; Scheres, L.; Zuilhof, H.; Chabal, Y. J.; Sueyoshi, T.; Kera, S.; Ueno, N.; Vilan, A.; Cahen, D. (Chem. Sci., 2012)

(untitled) - Segev, L.; Salomon, A.; Natan, A.; Cahen, D.; Kronik, L.; Amy, F.; Chan, C. K.; Kahn, A. (Phys. Rev. B: Condens. Matter Mater. Phys., 2006)